IDENTIFIKASI PENYELESAIAN SOAL BANGUN RUANG SISI LENGKUNG DITINJAU BERDASARKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Aripin, Usman (IKIP Siliwangi, 2021)
This research was carried out as a basis or preliminary study for further research by knowing the problem-solving ability in one of the MI in Cimahi . The research methode is used qualitative description. The subject in research that is the students of VI class of 32 students. Collecting technic of data is done test and non test. The test is competence the solving problem of math by four competence steps and non test is interviewed to 3 students by categhory of high competence. Medium and low. The result of the research is done the persentage solving problem of students math on bangun ruang item is one of MI in Cimahi as large as 39% could been category still low couse it. Because less comprehend on analizing question and less is given question not reguler to students.